Model Pengembangan Ketahanan Pangan Berbasis Pisang Melalui Revitalisasi Nilai Kearifan Lokal - Moch. Agus Krisno Budiyanto (Jurnal Teknik Industri, 2010)
This research aims to find” Food Endurance Development Model Based on Banana with Revitalisation Local Wisdom Value Reinforcement” . This model serve the purpose of basis for formulate public policy and education efforts and advocation public in the field of food to push national food endurance. Approach research that used in this qualitative research with qualitative descriptive design. Subject research is bapeda, development, agriculture official, farmer, elite figure, farmer group at regency Lumajang, Malang, and Blitar. Technique sampling that used snowball sampling. Data collecting method that used documentation, indepth interview, observation participatory, and limited discussion. Research data that got to analyzed with qualitative analysis (content analysis, and domain analysis). Based on research result inferential: 1) found banana production profile unity, distribution, consumption, and local wisdom character at regency Lumajang, Malang, and Blitar, 2) local wisdom character can be made principal focus in the effort develop food endurance based on banana, and 3) several important components and strategic of food endurance development model based on banana: a) local wisdom (foodstuff use reinforcement based on local, woman character, society/religion figure character, food self-supporting village, environment friendly agriculture, agriculture multiculture, and planning based on society), b) local government character (wisdom development prima tani, pilot projecting, capitalization, assistance, and tool of productions-distributions-marketing-consumption), and c) and character BPTP, BBMP, DUDI (pilot development projecting, capitalization, assistance, and system reinforcement productions-distributions-marketing-consumption).